2018
DOI: 10.1186/s12909-018-1389-6
|View full text |Cite
|
Sign up to set email alerts
|

Local anaesthesia training for undergraduate students – how big is the step from model to man?

Abstract: BackgroundLocal anesthesia is an important skill and a prerequisite for most dental treatments. However, the step from theory to application on the patient is huge for the novice. Hence, a mannequin training model course was developed and implemented into the existing local anesthesia curriculum in undergraduate dental students. It was the aim of this study to evaluate the relation between training-model and real-life anesthesia performance and to measure whether a gain in skill on the model translates to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 27 publications
1
30
0
1
Order By: Relevance
“…These findings were consistent with the results of studies by Hossaini and Kuscu et al 9,21 The manikin simulation models are static, which are far from being realistic. The major limitation of the manikin simulation models noted by the students was the unrealistic replication of anatomical structures; this concern was congruent with the findings of studies by Brand et al and Knipfer et al 22,23 This limitation may have affected students' responses to questions about finding the correct landmark and insertion points for injections. Although Knipfer et al found that an anesthesia success rate on manikin models did not imply an equal performance on patients, there were confounding factors in their study that would have affected the robustness of those findings, such as variations in anatomy, patients' behavioral reaction, and student inexperience in the procedure.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…These findings were consistent with the results of studies by Hossaini and Kuscu et al 9,21 The manikin simulation models are static, which are far from being realistic. The major limitation of the manikin simulation models noted by the students was the unrealistic replication of anatomical structures; this concern was congruent with the findings of studies by Brand et al and Knipfer et al 22,23 This limitation may have affected students' responses to questions about finding the correct landmark and insertion points for injections. Although Knipfer et al found that an anesthesia success rate on manikin models did not imply an equal performance on patients, there were confounding factors in their study that would have affected the robustness of those findings, such as variations in anatomy, patients' behavioral reaction, and student inexperience in the procedure.…”
Section: Discussionsupporting
confidence: 60%
“…However, the perceived confidence and anxiety in administering LA between the two did not differ significantly. 23 A dental robot patient has been developed in Japan that can perform specific movements and will help to reduce the effects of such confounders. Theme 1 emphasized this finding, which provided us with a deeper understanding of how students perceived the value of being on the receiving end of LA and that the sensation of feeling numbed could have made their transition to clinical practice easier.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This practicum can generate great anxiety and stress for the recipient and the surgeon but in our study, most of the student samples were calm or slightly nervous before and during administration of LA and only one participant out of the 71 was terrified. Instead, after the local anaesthetic was injected, the majority of the participants were calm and relaxed.…”
Section: Discussionmentioning
confidence: 69%
“…First aid education programmes, public health campaigns and formal first aid training are recommended in order to improve prevention, recognition and management of different injuries and illnesses [9]. A step from theory to application on patients is huge [10]. The traditional teaching methods are not always the most appropriate and effective [11].…”
Section: Introductionmentioning
confidence: 99%